Study of flavonoids and phenolic acids in green tea leaves - O. Yu. Maslov; S. V. Kolisnyk; M. A. Komisarenko; E. Yu. Akhmedov; S. M. Poluian; Z. V. Shovkova (Zaporozhye State Medical University, 2021)
The aim of work is study qualitative composition and quantitative content of flavonoids and phenolic acids in green tea leaves. Material and methods. The object of the study was green tea leaves, which were collected in Anhui Province, China. The analysis of 60 % ethanolic extract from green tea leaves was performed by high-performance liquid chromatography using a Prominence LC-20 Shimadzu chromatographic system (Japan) with an SPD-20AV spectrophotometric detector, an Agilent Technologies Microsorb-MV-150 column (reversed-phase, C18 modified silica gel, length - 250 mm, diameter - 4.6 mm, particles size - 5 μm). Identification of substances in the extract was carried out by comparing the retention time and the spectral characteristics of the test substances with the same characteristics of the reference standards. Results. 13 compounds were identified and determined by high-performance liquid chromatography. Among flavonoid aglycones quantitatively dominated by quercetin (0.35 %), in the case of flavonoid glycosides, it was luteolin-6-C-glycoside (1.30 %) and among phenolic acids, it was gallic acid (5.21 %). Conclusions. The qualitative composition, quantitative content of flavonoids and phenolic acids in the green tea leaves were determined by high-performance liquid chromatography. According to HPLC, the content of flavonoids in green tea leaves was higher than the content of phenolic acids.